Molecular structure and rheological properties of a poly(ethylene terephthalate) modified by two different chain extenders - Härth, Michael; Dörnhöfer, Andrea; Kaschta, Joachim; Münstedt, Helmut; Schubert, Dirk W. (Journal of Applied Polymer Science, 2020)
This paper compares the molecular structure and rheological properties of a commercial poly(ethylene terephthalate) (PET) after reactive processing with different concentrations of either pyromellitic dianhydride (PMDA) or a multifunctional epoxide (Joncryl®ADR‐4368) as a chain extender. By size exclusion chromatography with triple detection, an increase of molar mass, a broadening of molar mass distribution, and the generation of long‐chain branched molecules were found for both chain extenders. While gel‐free materials were obtained with PMDA, the processing with Joncryl leads to the formation of gels. The effect of branching, indicated by the Mark–Houwink exponent, is more pronounced for materials with Joncryl compared to PMDA and points to a more compact branching structure of the PET/Joncryl molecules. Rheological measurements in shear and elongation support the analysis from SEC and reveal a complex tree‐like branching structure for both chain extenders. In addition, the role of the two modifiers with respect to processing was assessed.<br